Pengaruh Kepercayaan (Trust) Dan Kualitas Pelayanan Online (E-Service Quality) Terhadap Keputusan Pembelian Online Shop Bukalapak - Ima Nurmanah; Edi Suswardji Nugroho (At-Tadbir : jurnal ilmiah manajemen, 2021)
This research was conducted with the aim of knowing how much influence Trust and E-Service Quality have on purchasing decisions at Bukalapak's online shop. This research uses descriptive verification method with a quantitative approach. The analysis used in this research is scale range analysis, path analysis. The test was conducted to test the validity, reliability test, t-test, f-test. Processed with the help of SPSS. Based on the results of the study, it was explained that Trust and online service quality (e-service quality) had a partial and simultaneous effect on purchasing decisions.Keywords: E-commerce, Trust, E-Service Quality, Purchasing Decisions.